(untitled) (CIPEEX, 2022)
BREAST CANCER IS THE SECOND MOST COMMON TYPE OF CANCER AMONG WOMEN IN THE WORLD AND IN BRAZIL, ACCOUNTING FOR ABOUT 28% OF NEW CASES EACH YEAR. COLORECTAL CANCER IS DEFINED AS TUMORS THAT AFFECT A SEGMENT OF THE LARGE INTESTINE (THE COLON) AND THE RECTUM. MUCH OF THESE TUMORS START FROM POLYPS, BENIGN LESIONS THAT CAN GROW ON THE INNER WALL OF THE LARGE INTESTINE. THIS STUDY AIMED TO REPORT THE CASE OF BREAST CANCER CONCOMITANT WITH A CANCER OF THE RECTUM WITH PULMONARY METASTASIS. A 42-YEAR-OLD WOMAN COMPLAINING OF A BREAST NODULE ON THE RIGHT BREAST, DIAGNOSED WITH INFILTRATING MAMMARY CARCINOMA INITIALLY TREATED WITH CHEMOTHERAPY, AND THEN WITH PARTIAL MASTECTOMY OF QSL. IN THE FOLLOW-UP, A CHEST COMPUTED TOMOGRAPHY SCAN REVEALED METASTASIS TO THE LUNGS. THE HISTOCHEMISTRY SHOWED THAT THE IMMUNOREACTIVE PATTERN INDICATED THAT IT WAS A COLORECTAL TRACT. WITH COLONOSCOPY, THE PRESENCE OF MALIGNANT NEOPLASIA OF THE RECTUM WAS OBSERVED, CULMINATING IN CHEMOTHERAPY, RADIOTHERAPY AND PARTIAL COLECTOMY AND LYMPHO- DRATOMY. THUS, THE TREATMENTS SUGGESTED FOR EACH NEOPLASIA AGREE WITH WHAT THE LITERATURE SHOWS AND THIS CASE CAN BE CLASSIFIED AS PRIMARY MULTIPLE NEOPLASIAS WHICH IS THE APPEARANCE OF A SECOND NEOPLASM WITH HISTOLOGY AND SITE DIFFERENT FROM THE FIRST. IN THIS CASE, IT ALSO HAD THE WORSENING OF A PULMONARY METASTASIS WHICH SHOWS US THE IMPORTANCE OF FOLLOW-UP AFTER THE DIAGNOSIS AND TREATMENT OF A FIRST NEOPLASM, SO THAT IT IS SUFFICIENT TO IDENTIFY RISK FACTORS AND TO IDENTIFY A SECOND PRIMARY MALIGNANT NEOPLASM.